2016
DOI: 10.1002/rob.21664
|View full text |Cite
|
Sign up to set email alerts
|

Survey Registration for Long‐Term Natural Environment Monitoring

Abstract: This paper presents a survey registration framework to assist in the recurrent inspection of a natural environment. Our framework coarsely aligns surveys at the image‐level using visual simultaneous localization and mapping (SLAM), and it registers images at the pixel‐level using SIFT Flow, which enables rapid manual inspection. The variation in appearance of natural environments makes data association a primary challenge of this work. We discuss this and other challenges, including 1) alternative approaches f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Unlike SpG/CNN, which is designed for general use, the STAR/GRIEF combination is not meant to handle large viewpoint changes and one should be cautious when applying it for general long-term navigation and localisation. For example, [61] evaluated the performance of several image features in a scenario of lakeshore monitoring, where the on-board camera aims perpendicularly to the vehicle movement and thus, the viewpoint changes are significant. The authors of [61] concluded that in their scenario, the ORB feature, which is based on BRIEF, slightly outperformed the other features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike SpG/CNN, which is designed for general use, the STAR/GRIEF combination is not meant to handle large viewpoint changes and one should be cautious when applying it for general long-term navigation and localisation. For example, [61] evaluated the performance of several image features in a scenario of lakeshore monitoring, where the on-board camera aims perpendicularly to the vehicle movement and thus, the viewpoint changes are significant. The authors of [61] concluded that in their scenario, the ORB feature, which is based on BRIEF, slightly outperformed the other features.…”
Section: Discussionmentioning
confidence: 99%
“…For example, [61] evaluated the performance of several image features in a scenario of lakeshore monitoring, where the on-board camera aims perpendicularly to the vehicle movement and thus, the viewpoint changes are significant. The authors of [61] concluded that in their scenario, the ORB feature, which is based on BRIEF, slightly outperformed the other features.…”
Section: Discussionmentioning
confidence: 99%
“…However, Valgren and Lilienthal [205] have shown that these representations are not well suited for similarity association across season cycles. GRIEF local descriptor [87] (derivatives of BRIEF [24]) or ORB feature [61] show better results for this task. The use of heterogeneous databases (i.e.…”
Section: Appearance Changesmentioning
confidence: 95%
“…Desc. Used in VBL Pseudo Corners detector [129] Point [129,130] Hessian-affine [126] Point [71,2,100,173,4] FALoG [216] Point [49] SIFT [109] Point [188,181,103,223,224,140,220] RootSIFT [3] Point [125,4,173,199,200] SURF [18] Point [44,100,190,158,188,205] ORB [169] Point [61] BRIEF [24] Point [90,87] BRISK [94] Point [49,125,133]…”
Section: Namementioning
confidence: 99%
“…To date, a range of ASVs have been developed [6][7][8][9][10], however, most are large vehicles that have been designed for operation in marine environments and lakes [7,8,11]. They rely on unsuitable sensor packages and lack the control accuracy required for operation in SFPs or wet silos.…”
Section: Review Of Existing Asvsmentioning
confidence: 99%